2017
DOI: 10.4251/wjgo.v9.i1.4
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic approaches to metastatic gastroenteropancreatic neuroendocrine tumors: A glimpse into the future

Abstract: Neuroendocrine (NE) gastroenteropancreatic tumors are a heterogeneous group of neoplasias arising from neuroendocrine cells of the embryological gut. Their incidence have increased significantly over the past 3 decades probably due to the improvements in imaging and diagnosis. The recent advances in molecular biology have translated into an expansion of therapeutic approaches to these patients. Somatostatin analogs, which initially were approved for control of hormonal syndromes, have recently been proven to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 125 publications
(190 reference statements)
1
11
1
2
Order By: Relevance
“…Nevertheless, in both the European Neuroendocrine Tumor Society (26,27) and the North American Neuroendocrine Tumor Society (28,29) consensus guidelines for diagnosing and treating PC patients, somatostatin analogs are mentioned as a treatment option. According to recent findings, SSAs are not only involved in the control of hormonal syndromes, but they also have a role as antiproliferative agents in neuroendocrine tumors (9,30). Benefit of the SSA treatment with octreotide, lanreotide or 177 Lu-DOTATATE for patients with metastatic pulmonary carcinoid tumor has been shown by multiple studies and was also confirmed in our study (31)(32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, in both the European Neuroendocrine Tumor Society (26,27) and the North American Neuroendocrine Tumor Society (28,29) consensus guidelines for diagnosing and treating PC patients, somatostatin analogs are mentioned as a treatment option. According to recent findings, SSAs are not only involved in the control of hormonal syndromes, but they also have a role as antiproliferative agents in neuroendocrine tumors (9,30). Benefit of the SSA treatment with octreotide, lanreotide or 177 Lu-DOTATATE for patients with metastatic pulmonary carcinoid tumor has been shown by multiple studies and was also confirmed in our study (31)(32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 87%
“…Pancreatic neuroendocrine tumors (pNETs) represent approximately 7% of all NETs. Their prevalence has considerably increased over the last three decades, which is primarily due to improvements in imaging and diagnostic techniques (1,2). Despite the increased diagnosis of incidental lesions, 40-95% of patients present with a metastatic disease at the first diagnosis (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Other treatments for GEP-NET include molecular targeted therapy, chemotherapy and peptide receptor radionuclide therapy (PRRT). For liver metastases, surgical resection, hepatic artery embolization (HAE), selective internal radiation therapy (SIRT) and radiofrequency ablation (RFA) or microwave ablation (MWA) can be performed [4][5][6].…”
Section: Introductionmentioning
confidence: 99%